2008
DOI: 10.1259/bjr/77979574
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pancreatic pseudocyst-portal vein fistula presenting with pancreatic ascites: strength of MR cholangiopancreatography

et al.

Abstract: Pancreatic pseudocyst-portal vein fistulae are a very rare complication of acute or chronic pancreatitis. Another late complication of chronic pancreatitis is pancreatic ascites. We report the case of a 43-year-old man with a spontaneous pseudocyst-portal vein fistula presenting with pancreatic ascites diagnosed by various imaging modalities, in order to emphasize the strength and efficacy of magnetic resonance cholangiopancreatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…There are, however, reports of pancreatic pseudocysts communicating with the portal vein. 2,3 That is attributed to pancreatic enzyme-rich fluid causing…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, reports of pancreatic pseudocysts communicating with the portal vein. 2,3 That is attributed to pancreatic enzyme-rich fluid causing…”
Section: Discussionmentioning
confidence: 99%
“…Only 17 cases of pancreatic pseudocyst connecting with the portal venous system have been reported [4][5][6]. Several reports indicated that activated pancreatic enzymes in the pseudocyst might cause inflammation and directly contribute to cyst wall fragility and failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that activated pancreatic enzymes in the pseudocyst might cause inflammation and directly contribute to cyst wall fragility and failure. These enzymes also cause erosion of the portal wall and induce venous thrombosis [4,7]. Spontaneous rupture of the pancreatic cyst occurred in about 5% of patients [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One uncommon mechanism for bleeding in pancreatitis is the spontaneous rupture of a pseudocyst. Pseudocysts have been documented to spontaneously decompress by rupture into the stomach, 2 the small intestine, the colon as well as the portal vein 3 . Other mechanisms for bleeding in pancreatitis include portal hypertensive bleeding in the setting of extra‐hepatic portal hypertension due to splenic vein thrombosis, and rupture of a splenic artery or splenic artery aneurysm.…”
mentioning
confidence: 99%